Potential Tourism of Cultural Heritage in Nusa Penida Bali Indonesia - Nuruddin,; Pujiastuti, Sri; Kristianto, Yohanes; Semara, I Made Trisna; Wirawan , Putu Eka (International Journal of Psychosocial Rehabilitation, 2020)
As one of the leading destinations in Indonesia, Bali is always innovating so that foreign tourists do not feel bored, so many new destinations have emerged along with fulfilling adequate infrastructure, one of which is Nusa Penida Island, Nusa Lembongan and Nusa Ceningan commonly called Tri Ning Nusa along with third of the pier to be built. The focus of this study is to look at the cultural potential of local people who can support the development of attractions in the islands, especially in Nusa Penida. The writing method used is literature review, especially in articles in journals and mass media that have been published online. This study produces findings that in the Nusa Penida Islands there are several cultural potentials that support tourist destinations that have been relying on nature and the sea, one of which is Rejang Renteng Dance, Kain Tenun Rangrang and Kain Tenun Cepuk. In general, these three cultural heritages have been carried out in accordance with the commodification of the market. However, the problem of marketing and capital is still something that must be corrected, so that the quantity can be increased and the quality of life can help local people.